Perception of the disease as determinant of illness acceptance in patients with psoriasis - Adamska, Marta; Juczyńska, Katarzyna; Miniszewska, Joanna (Current Problems of Psychiatry, 2015)
Disease acceptance is a problem for many patients which they are struggling with throughout its duration. Modifying the perception and importance of the disease, thus increasing its acceptance, may have a positive impact on patients’ involvement in the treatment process and their general well-being. The aim of our study was to examine the level of disease acceptance and the way of perception of the disease in groups of hospitalized and outpatient psoriasis patients. The study comprised 61 hospitalized and ambulatory - treated psoriasis patients. The following measures were employed: Acceptance of Illness Scale (AIS), The Disease - Related Appraisals Scale (DRAS), Self-administered Psoriasis Area and Severity Index (SAPASI), Visual Analogue Scale (VAS). The examined patients accepted their illness to an average extent. Patients in both groups similarly assessed their disease - most commonly in life-threatening terms, most rarely in terms of profit and value. In the hospitalized patients’ perception of the disease as a life-threatening event, harm, obstacle/loss and importance correlated negatively with the illness acceptance. In the group of ambulatory patients, percepting of the disease as a life-threatening event and harm, negatively correlated with its acceptance. The assessment of disease in terms of obstacle/loss allowed for predicting the level of its acceptance in patients with psoriasis. The obtained results confirm the validity of psychological interventions in psoriasis patients aimed at modifying the way of assessment and the perception of patient’s health situation.